Geography education in Ghanaian senior high schools: a qualitative study of the gender differences in students' geographical knowledge and interests. Issue 4 (29th September 2021) - Opoku, Foster
Abstract: Although, a number of studies exists regarding students' experiences of Geography as a school subject, the gender differences in students' geographical knowledge and interests are rarely recognised. Drawing from the cognitive interest theory, and using a qualitative phenomenological design, this study explored the gender differences in the geographical knowledge and interests of 48 Ghanaian senior high school students. In-depth interviews were conducted with 24 males and 24 females, sampled from two public schools in the Kumasi Metropolis of the Asante Region. Data obtained were analysed thematically, with specific normative and subjective views of participants presented as direct quotations. Both gender demonstrated appreciable level of knowledge regarding the subject matter of Geography and its relevance to daily life experiences. Gender differences were, however, observed in students' understanding of the subject matter of Geography and conceptions of the importance of Geography. Congruent to the cognitive interest theoretical perspective, the findings suggest that there is a considerable link between geographical knowledge and geographical interests of both gender. The study findings have the potential of informing policy and curricula changes by relevant stakeholders to help bridge the gender imbalances in school Geography enrolments and also to secure the success of Geography.